Australian Foster Carers' Views and Concerns Regarding Maternal Drug Use and the Safety of Breastmilk - Stacy Blythe; Kath Peters; Emma Elcombe; Elaine Burns; Karleen Gribble (MDPI AG, 2021)
Parental substance misuse and mental health issues are major factors associated with infant placement into out-of-home care. Such placements may result in disruption and/or cessation of breastfeeding. Provision of breastmilk to infants in out-of-home care (OOHC) is desirable in terms of infant health and development, and also in supporting maternal caregiving. However, little is known about how breastfeeding is supported for infants in out-of-home care. This study used an online survey to explore the facilitation of breastfeeding in the context of OOHC and foster carers' management of expressed breastmilk (EBM). Foster carers were generally open to the idea of maternal breastfeeding and infants in their care receiving EBM from their mothers. However, the majority of respondents expressed concern regarding the safety of EBM for infant consumption due to the possibility of harmful substances in the milk. Concerns regarding the safety of handling EBM were also prevalent. These concerns caused foster carers to discard EBM. Findings suggest foster carers' may lack knowledge related to maternal substance use and breastmilk. Better integration between health care and social service systems, where the voices of mothers, foster carers and child protection workers are heard, is necessary to develop solutions enabling infants living in OOHC access to their mother's breastmilk.